Regulations Against Human Trafficking: A Comparison of Indonesia and Vietnam - Yufa Verlita; Siti Rahayu Ramadhani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Human trafficking is a complex transnational crime and a serious threat to human rights. This article examines the legal frameworks and countermeasures against human trafficking in Indonesia and Vietnam, focusing on legislation, implementation, and victim protection. In Indonesia, although Law No. 21 of 2007 on the Eradication of the Crime of Human Trafficking and several supporting regulations have been enacted, their implementation still faces challenges, particularly in law enforcement and victim identification. In contrast, Vietnam has taken more progressive steps by incorporating strict criminal sanctions in its Penal Code and enacting Law No. 66/2011/QH12 on the Prevention and Combat of Human Trafficking, which is more operational and holistic. The 2024 amendment to this law and the adoption of a comprehensive national program demonstrate Vietnam’s commitment to aligning domestic policies with international standards. Based on these findings, the article recommends that Indonesia adopt several of Vietnam's best practices, such as strengthening regulations to cover all forms of exploitation, enhancing victim protection mechanisms, and expanding international cooperation. With a more integrated approach, Indonesia is expected to improve the effectiveness of its efforts to combat human trafficking comprehensively.